Non-linear dynamical analysis of laminated reinforced composite doubly curved shallow shells - Bich, Dao Huy; Long, Vu Do (Vietnam Journal of Mechanics, 2007)
The present paper deals with a non-linear dynamical analysis of laminated reinforced composite doubly curved shallow shells. The motion equations of shell based upon the thin shell theory considering the geometrical non-linearity and the Lekhnitsky's smeared stiffeners technique. Simultaneous ordinary differential equations are obtained by means of Bubnov-Galerkin's procedure. Non-linear responses are calculated by using an iterative procedure in conjunction with Newmark constant acceleration scheme. Obtained results allow to discover the influence of stiffeners, the shell geometry on the non-linear response of eccentrically stiffened laminated composite shells